ON SPEKTRUM OF A SELF ADJOINT DIFFERANTIAL OPERATOR OF HIGHER ORDER WITH UNBOUNDED OPERATOR COEFFICIENT AND ASYMPTOTIC BEHAVIOUR OF EIGENVALUES - Adiguzelov, Ehliman; Sezer, Yonca (YILDIZ TECHNICAL UNIV, 2006)
In this work, spectrum of a self adjoint differantial operator of higher order with unbounded operator coefficient has been investigated and an asymptotic formul for the eigenvalues of this differantial operator have found
Keywords: Hilbert space; eigenvalue; spectrum; resolvent; closable operator; symmetric operator; self adjoint operator; Engineering